MENINGKATKAN KINERJA GURU MELALUI SUPERVISI AKADEMIS DENGAN PENDEKATAN PEMBELAJARAN MODELING TERHADAP GURU MATA PELAJARAN KIMIA PADA SEKOLAH BINAAN - Artiana Artiana (Universitas Lambung Mangkurat, 2014)
Abstract. Ability of teachers to create learning tools based approach to modeling and implementing the device in the learning process is a component of teacher performance is the goal of the research so by increasing the performance of teachers are expected to improve learning outcomes chemistry students in grade XI SMAN 2 Central Dusun and SMAN 1 Awang Lapai. This study uses two cycles each cycle consisting of the stages of planning, action, observation and reflection. The subjects were two chemistry teachers XI IPA SMAN 2 Central Dusun and SMAN 1 Awang Lapai. The results showed an increase in the ability of chemistry teachers XI IPA SMAN 2 Central Dusun in drafting device modeling approach based learning by 58% in the first cycle to 86.5% in the second cycle and at SMAN 1 Awang Lapai amounted to 64.75% in the first cycle to 86.5% in the second cycle. Similarly, in implementing device modeling approach based learning in SMAN 2 Central Dusun 71.5% and 86.5% in the second cycle. The ability of chemistry teachers XI IPA SMAN 1 Awang Lapai in implementing the device in the learning process increased by 67.5% in the first cycle to 86% in the second cycle. In the modeling approach learning with students and teachers have a positive response, visible enthusiasm in the learning process.Keywords: performance of teachers, academic supervision, modeling learning approaches